Factors Affecting Survival Trend in Colorectal Cancer- A Hospital Based Study (TAJ: Journal of Teachers Association, 2019)
Colorectal carcinoma is the second most common malignancy and the second leading cause of cancer deaths in Western countries. The condition becomes increasingly common over the age of 50 years. The total number of colorectal cancer patients available for the study within the stipulated time was 56. Among them 64.29% patients were male and 35.71% patients were female. 01.79% patient belonged to age group ≤ 20, 12.5% belonged to age group 21-30, 19.64% belonged to age group 31-40, 25.0% belonged to age group 41-50, 26.79% belonged to age group 51-60, 08.93% belonged to age group 61-70 and 05.35% patients were >70 years of age. Mean age was 48.05 years ± 13.97 SD. In our study, 27.2% survived ≤3 months, 36.4% 4-6 months, 09.1% 7-9 months, 18.2% 10-12 months, 09.1% 13-24 months and 0% >24 months. Among 11 expired patients, 03 got curative treatment and rest of 08 got palliative treatment. Those who got curative treatment, 66.7% survived 10-12 months and 33.3% 13-24 months. Those who got palliative treatment 37.5% survived ≤3 months, 50.0% 4-6 months and 12.5% 7-9 months. Overall median survival was 07 months, for curative treatment 15 months and for palliative treatment 05 months.TAJ 2018; 31(2): 12-16